Sustainability of traditional food entrepreneurs amid Covid-19 pandemic - Adilah Md Ramli; Shalawati Ibrahim; Sylvester Mantihal (Faculty of Food Science and Nutrition, UMS, 2025)
This study examines the impact of the COVID-19 pandemic on local entrepreneurs in Malaysia, focusing on those selling traditional food in Selangor and Sabah. Using a qualitative approach, interviews were conducted with 20 entrepreneurs from diverse backgrounds across the two states. Open-ended, semi-structured questions were employed to gather detailed insights, and the responses were transcribed, categorised, coded and analysed thematically. From the analysis, one theme emerged. The theme identified is sustainability (coded: adaptation to technology). Entrepreneurs in both states adopted new strategies, including social media and e-commerce, to sustain their businesses during the pandemic. Their willingness and ability to embrace these changes differed according to demographic factors as they navigated the challenges of relearning and adapting with current market trends.